(R)‐α‐Trifluoromethylalanine as a 19F NMR Probe for the Monitoring of Protease Digestion of Peptides. (18th November 2021) - Devillers, Emmanuelle; Chelain, Evelyne; Dalvit, Claudio; Brigaud, Thierry; Pytkowicz, Julien
Abstract: Fluorinated non‐natural amino acids are useful tools for improving the bioavailability of peptides but can also serve as fluorinated probes in 19 F NMR‐based enzymatic assays. We report herein that the use of the non‐natural α‐quaternarized ( R )‐α‐trifluoromethylalanine (( R )‐α‐TfmAla) provides convenient and accurate monitoring of trypsin proteolytic activity and increases resistance towards pepsin degradation. Abstract : A useful fluorinated NMR probe : α‐Quaternarized ( R )‐α‐trifluoromethylalanine (α‐TfmAla) is a good tool for providing convenient and accurate 19 F NMR‐based monitoring of trypsin proteolytic activity and increases resistance towards pepsin degradation.